Religion in the Legacy of Nikita Shapoval - Kondratyk, Leonid Josypovyč (Ukrai͏̈ns'ke relihijeznavstvo, 2004)
One of the pressing problems of contemporary Ukrainian religious studies is the study of its own history, some of which were either deformed or silenced in Soviet times. The practice of silence primarily concerned representatives of the Ukrainian revival of the early twentieth century, who, through their socio-political and scientific activities, asserted the right of the Ukrainian nation to independent development. The cohort of these prominent figures included Nikita Shapoval (1882-1932). Studying his religious heritage is important in view of the following points: first, it will make it possible to understand the history of our religious studies in its totality, and secondly, to expand the range of ideas, concepts, provisions for addressing the pressing issues that the national is working on religious studies. One of the most important issues is the nature and functionality of religion.